Mexico : Arrangement Under the Flexible Credit Line and Cancellation of Current Arrangement-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2019)
This paper discusses Mexico's Arrangement Under the Flexible Credit Line and Cancellation of Current Arrangement. Fiscal policy has stemmed the rise in the public debt ratio in the past two years; a very tight monetary policy stance has helped reduce headline inflation to the central bank's target; and financial supervision and regulation are strong. The flexible exchange rate is playing a key role in the economy's adjustment to external shocks. The Mexican economy, nonetheless, remains exposed to external risks, including renewed volatility in global financial markets, increased risk premia, and a sharp pull-back of capital from emerging markets, as well as continued uncertainty about Mexico's trade relations with the United States. The new arrangement under the Flexible Credit Line (FCL) will continue to play an important role in supporting the authorities' macroeconomic strategy by providing insurance against tail risks and bolstering market confidence. The proposed new commitment and cancellation of the current arrangement would have a net positive impact on the Fund's liquidity position.